2020
DOI: 10.1002/smll.202002440
|View full text |Cite
|
Sign up to set email alerts
|

Multistimuli Sensing Adhesion Unit for the Self‐Positioning of Minimal Synthetic Cells

Abstract: Cells have the ability to sense different environmental signals and position themselves accordingly in order to support their survival. Introducing analogous capabilities to the bottom‐up assembled minimal synthetic cells is an important step for their autonomy. Here, a minimal synthetic cell which combines a multistimuli sensitive adhesion unit with an energy conversion module is reported, such that it can adhere to places that have the right environmental parameters for ATP production. The multistimuli sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…With these modules, the synthetic cell is able to use the presence of light, non‐oxidative conditions, neutral pH, and the presence of metal ions in order to determine if it will adhere to a particular surface. [ 136 ] It is this complex multi‐stimulation sensing ability that will allow synthetic cells to approach the complexity of environmental interaction that is apparent in live cells.…”
Section: Inter‐cellular Communication and Environment Interactionmentioning
confidence: 99%
“…With these modules, the synthetic cell is able to use the presence of light, non‐oxidative conditions, neutral pH, and the presence of metal ions in order to determine if it will adhere to a particular surface. [ 136 ] It is this complex multi‐stimulation sensing ability that will allow synthetic cells to approach the complexity of environmental interaction that is apparent in live cells.…”
Section: Inter‐cellular Communication and Environment Interactionmentioning
confidence: 99%
“…Such structures can be formed by the encapsulation of lipid-bounded aqueous droplets and biomolecule complexes, within a host (envelope) droplet [17,18], where each droplet may contain different biochemical species. Recent work has demonstrated that organelle-like components can work as functional units to process molecular signals [19,20], regulate sequential reactions [21,22,23], and may be used for energy harvesting [24] within artificial cells. Furthermore, compartmentalisation has been harnessed in similar ways in the packing and patterning of individual protocells to construct more complex, functional, tissue-like materials, incorporating protein channels [25], DNA sequences [26], and functional hydrogels [27].…”
Section: Main Textmentioning
confidence: 99%
“…Remarkably, one of their main appeals-the ability to harness solar energy-remains to this day almost entirely unexplored. Regarding orthogonality, the growing portfolio of light-switchable components in SynBio, such as optogenetic tools (which sometimes rely on similar proteins) or dimerizable proteins for localization (45), requires additional care to avoid undesired cross talk and coactivation. In contrast, only a few chemically driven proton pumps for energy regeneration have been reported.…”
Section: Energy Supply To Drive Cellular Processesmentioning
confidence: 99%
“…Notably, to the best of our knowledge, this bottom-up organelle was the first to harness solar energy to drive protein synthesis (54), highlighting the potential for autonomous and sustainable operation. An energy module with the above composition was also used in combination with a multi-stimuli-sensitive adhesion unit able to sense light, metal ions, oxidative stress, and pH, resulting in its localization in an optimal environment (45). Furthermore, the same light-driven energy module was used to control the beating frequency of flagella via activation of axonemal dyneins (55).…”
Section: Energy Supply To Drive Cellular Processesmentioning
confidence: 99%